Chaos-based audio encryption: Efficacy of 2D and 3D hyperchaotic systems - Thejas Haridas; Upasana S.D.; Vyshnavi G.; Malavika S. Krishnan; Sishu Shankar Muni (Franklin Open, 2024)
Secure communication in the digital age is necessary; securing audio data becomes very critical since this is normally transmitted across susceptible networks. Traditional approaches to encryption, like Advanced Encryption Standard and Rivest–Shamir–Adleman, are pretty solid but mostly too computationally intensive for real-time audio applications. This paper presents a new audio encryption scheme using chaotic systems, characterized by high sensitivity to initial conditions, pseudo-randomness, and determinism. These properties make chaotic systems ideal for generating keys for cryptographic purposes. Indeed, complex keys that would be nearly impossible to reverse-engineer without exact initial parameters can be obtained with them. This methodology first digitizes the audio signal and subsequently encrypts each sample according to chaotic sequences from multiple systems, like 2D Memristive Hyperchaotic Maps and 3D Hyperchaotic Quadratic Maps. The encryption processes enormously increase the randomness of the encrypted audio and blind the original data, demonstrating the strength of the chaotic systems in securing audio information.Simulation of this encryption approach confirms its effectuality in providing strong security for audio data while maintaining efficiency, thus being suitable for real-time applications. The developed encryption schemes show high resistance to differential attacks, while the quality of the encrypted audio remains acceptable after transformation. This result can demonstrate chaotic systems’ potential to provide a secure and efficient solution for audio communications, which has broad applications in telecommunications, military communications, and confidential conferencing systems. This work, described in the paper, thus satisfies the growing demand for robust security in digital communications and opens up avenues of future research toward chaotic parameter optimization and an extension to other forms of data, enhancing the security features in all types of digital communication channels.